Response of upland taro (Colocasia esculenta) to varying water regimes under humid tropical conditions of India (Current Horticulture, 2024)
The field experiment was conducted on taro (Colocasia esculenta L. Schott) during 2017, 2018 and 2019 with three spells of irrigation (irrigation for 2 months and remaining period under stress, irrigation for 4 months and remaining period under stress, irrigation for 6 months) and four levels of drip irrigation, viz. 75%, 100%, 125% and 150% of water requirement of the crop (ETc) in factorial design. Pooled analysis of three years data revealed significant difference in growth and yield as well as water-use efficiency under stress and non-stress conditions. Moisture stress two and four months after planting resulted in reduction in leaf area index (-21 and -19%), number of tillers ( -27 and -6%), root to shoot ratio (-60 and -43%), cormel to corm ratio (-69 and -53%), cormel yield (-58 and -28%), water-use efficiency (-32 and -36%) and increase in corm yield (+34 and +52%) respectively, compared to no stress. Drip irrigation for six months @ 100% ETc recorded optimum growth, cormel yield (21.08 tonnes/ha) with water-use efficiency (0.4 g/L) in upland condtion.
Keywords: Cormel yield; Drip irrigation; Water stress; Water-use efficiency